A COMPARATIVE STUDY OF EFFICACY AND TOLERABILITY OF GENERIC AND ORIGINAL LOW-DOSE BISOPROLOL/HYDROCHLOROTHIAZIDE COMBINATION IN PATIENTS WITH ARTERIAL HYPERTENSION OF 1-2 DEGREES. RESULTS OF CLINICAL RANDOMIZED CROSSOVER STUDY - S. Yu. Martsevich; S. N. Tolpygina; A. V. Zakharova; V. P. Voronina; O. V. Lerman; Yu. V. Lukina; N. A. Dmitrieva; N. V. Kiseleva (Столичная издательская компания, 2015)
Aim. To study the clinical equivalence of the two low-dose combined drugs on the base of generic and original bisoprolol and hydrochlorothiazide (HCTZ): BISANGIL® (Ozon, Russia) and LODOZ® (NYCOMED, Merck KGaA, Germany) in patients with arterial hypertension (HT) of 1-2 degrees.Material and methods. Patients with HT of 1-2 degrees (n=30; 11 men and 19 women; aged 62.7±10.7 years) were included in open crossover randomized trial. Duration of the study for each patient was 18 weeks: two 6-week courses of active treatment with each drug and two 2-week washout periods prior to each treatment course. The sequence of treatment courses was determined by randomization. Increase in bisoprolol dose and/or amlodipine addition occurred when effect was not sufficient. Therapy effectiveness (office blood pressure (BP), heart rate) and safety was monitored at visits.Results. BP reduction after 6 weeks of therapy was -21.6±11.1/10.4±11.3 mm Hg in LODOZ® group and -22.9±9.7/11.7±13.5 mm Hg in BISANGIL® group (p<0.0001 for both), intergroup differences were insignificant. Target BP after 6 weeks of therapy was achieved in 26 (87%) and 28 (93%) patients, respectively.Conclusion. The therapeutic equivalence of the studied fixed combinations of bisoprolol/HCTZ was demonstrated in treatment of patients with HT of 1-2 degrees.